TRILEMA GLOBALISASI; DINAMIKA DEMOKRASI DAN KEDAULATAN DALAM FENOMENA BREXIT - Muhammad Badaruddin (Jurnal Ilmu dan Budaya, 2016)
As globalization has been fading away with subsequent consequences in 2008 financial crises, the current world is now witnessing further negative impacts on wider aspects social, economic, political and security. Such a catastrophic constellation of present-day with Trump’s words that resembles this ‘globalismo-phobia’ and the move of Britain Exit as a manifestation of threat of such sacred phrase like free trade and global migration—poses a big problem on where we are to go. What could a democracy give its solution to this and how should sovereignty be defined and developed? The paper shall discuss this issue, using Dani Rodrik’s framework of  globalization trimemma. It is the finding of the writer that while alliance and unions of several nation-states may take place, a given nation-state remains an autonomous variable that may play its dynamic role in world politics.